Environmental education in times of pandemics: an experience at the Educational Institution Liber, João Monlevade, Minas Gerais (Research, Society and Development, 2021)
The objective of this work was to promote a participatory learning process about solid waste. The study was developed during the pandemic caused by COVID-19, at the Liber Education Institution, linked to the DOCTUM Education network, located in João Monlevade, Minas Gerais, from April to December 2020 and had the participation of 120 students of elementary school. This project was developed in four stages, the first being the application of a questionnaire in order to gather information on how families deal with the issue of recycling in their daily lives. In the second stage, lectures, dynamics and workshops were held with students to help them understand the concepts of conscious consumption and solid waste recycling, as well as the importance of generating fertilizer from solid solid waste. In the third stage, the students made a pedagogical toy from recycled materials and, in a fourth stage, the assembly of simple composters was carried out by students and families, seeking to share knowledge between students and their parents, teachers at the school. and extension workers during a pandemic. With the development of the project, the students understood the biological processes that occur naturally in the environment and the benefits and potential of organic fertilization for the production of healthier foods, in addition to the importance of conscious consumption and solid waste recycling. The project showed that environmental practices in schools are fundamental in consolidating socio-environmental attitudes, since the school is a promoter of knowledge and citizenship, and must meet the socio-environmental concerns of its students.